Empirical Analysis of Banking Sector, Stock Market and Economic Growth Nexus in Nigeria - , Eugene Iheanacho (Archives of Current Research International, 2018)
This explores the direction of the causal relationship between banking, stock market and economic growth, while controlling for relevant variables in Nigeria for the period 1981–2014. Using principal component analysis for the construction of the financial development indices, Auto-regressive Distributed Lag (ARDL) and the Granger causality approach. Our results are in three folds: First, the causal effect of stock market development on economic growth is found to be positively significant in the long-run and short-run but bank sector development is found to be positively insignificant suggesting the weakness of financial intermediary sector in resource mobilisation and allocation in Nigeria. Second, this study finds no causality running from economic growth to financial development in both at the long run and short run positions. Third, the causal effect of macroeconomic variables on finance-growth nexus is found to be uni-directional in the long-run, suggesting that crude oil price and government expenditure are the key drivers of long-term development of the Nigerian financial sector and as such among the underlying factors that determine the amount of economic activities passing through the Nigerian financial sector. The policy recommendation is to make the banking sector more accessible to enhance financial deepening and indeed a policy that will encourage diversification of the economy rather than solely dependence on oil revenue.